Tom and Casy arrive at Uncle John's farm - Thomas Hart Benton (artist):::Creator::::::::::::
Illustration of Tom Joad and Jim Casy as they arrive at the Uncle John's farm from The Grapes of Wrath, vol.1 p. 82, illustrated edition, by Thomas Hart Benton, a native of eastern Oklahoma, who was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate. "They saw the tank legs now, and the house, a square little box, unpainted and bare, and the barn, low-roofed and huddled. Smoke was rising from the tin chimney of the house. In the yard was litter, piled furniture, the blades and motor of a windmill, bedsteads, chairs, tables. 'Holy Christ, they're fixin' to go.' Joad said."